EXPLORING STUDENTS' SELF - EFFICACY TOWARDS THEIR SPEAKING SKILL AT MTsN 1 MAROS - Inul; Nuraeni; Tanasy, Novaliya; Fachrunnisa, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aimed to explore the influence of students' self-efficacy on their English-speaking skills at MTsN 1 Maros. This study employed a qualitative method, with data collected through interviews and observations. The population of this research consisted of ninth-grade students at MTsN 1 Maros, and a purposive sampling technique was used to select six participants representing varying levels of self-efficacy. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing/verification. The findings reveal that students with high levels of self-efficacy tend to be more confident, willing to face speaking challenges, able to regulate their emotions, and capable of applying their speaking skills in a variety of contexts both inside and outside the classroom. They also show greater tolerance for mistakes and possess intrinsic motivation to continue practicing. On the other hand, students with low self-efficacy tend to avoid speaking tasks, experience anxiety, and feel more comfortable in structured or guided speaking situations. The three dimensions of self-efficacy magnitude, strength, and generality were found to significantly influence students' engagement in speaking activities. These findings highlight the importance of fostering students’ self-efficacy through consistent practice, social support, and a psychologically safe learning environment.